Perilaku Adopsi E-Commerce Usaha Mikro Kecil Menengah (UMKM) Makanan dan Minuman di Masa Pandemi COVID-19 - Arman Jauhari; Mukhamad Najib; Mimin Aminah (Jurnal Manajemen dan Organisasi, 2022)
The Corona Virus Disease 2019 (COVID-19) pandemic has had an impact on the economy, especially in sales of Micro, Small and Medium Enterprises (MSMEs) in Indonesia. In order to reduce the impact of the pandemic, the Government of Indonesia has imposed a Large-Scale Social Restriction Policy (PSBB) in a number of regions in Indonesia. This policy makes MSMEs have to rely on technology to run their operations, so the adoption of E-commerce is a must for MSMEs. The purpose of this study is to analyze the factors that influence the adoption of E-commerce in the COVID-1 9pandemic with a modified Technology Accessibility Model (TAM) approach. This research was conducted at an organization that oversees a number of SMEs in the city of Bogor, namely the Paguyuban. The sample in the study was MSMEs under the auspices of the Association that used E-commerce during the COVID-19 Pandemic in Bogor City. The total sample in this study amounted to 155 respondents. The analysis technique used is Structure Equation Modeling Partial Least Square (SEM-PLS). The results of this study indicate that the behavior of using E-commerce in MSMEs in Bogor City is influenced by the ability to adopt E-commerce attitudes. A good adoption attitude towards the use of E-commerce can be influenced by the perceived usefulness and technology readiness factors. Organizational readiness and perceived convenience do not have a significant effect on increasing the attitude of E-commerce adoption in the MSME Association which focuses on selling food and beverages in the city of Bogor.